Did destructive leadership help create the conditions for the spread of Covid-19, and what are the early warning signs?. (February 2023) - Sadler Smith, Eugene; Akstinaite, Vita
This research asks: 'were there any objectively identifiable signals in the words leaders used in the early stages of the Covid-19 pandemic that can be associated with ineffective management of the crisis?' We chose to focus on the leaders of the two English-speaking nations that fared worst and best in the pandemic, the United States and New Zealand. By way of background and in order to contextualise the research, we compared and contrasted Trump's and Ardern's leaderships using the toxic triangle framework of destructive leadership. We then focused on the leader behaviour element of the triangle by using computerised text analysis (CTA) to analyse Trump's and Ardern's public pronouncements during the critical early stages of the pandemic. Based on a similarity index ( S ), we identified linguistic markers associated with destructive leader behaviours and negative outcomes (Trump) and non-destructive leader behaviours and positive outcomes (Ardern). We discuss future applications of these linguistic markers for the diagnosis both of incumbent and potential leaders' responses to crises management.